Hannah Arendt's machines: Re-Evaluating marketplace theory in the AI era. Issue 1 (2nd January 2020) - Schroeder, Jared
ABSTRACT: Artificially intelligent communicators are increasingly influencing human discourse. Algorithms and bots are determining the range and frequency of ideas individuals encounter, ultimately raising questions about whether the marketplace of ideas theory of the First Amendment, as it has traditionally been envisioned by the Supreme Court, can continue to endure as justices' dominant tool for rationalizing extensive safeguards for free expression. In particular, the emergence of AI actors, which drown out human ideas and spread false and misleading information, appear to only worsen the long-standing criticisms of the theory's assumptions. This article draws from Hannah Arendt's political philosophy to construct a revised approach to marketplace theory as it enters its second century of use by the Supreme Court. Arendt's ideas, especially as they pertain to the power of human-made machines to condition human behavior, as well as her concerns regarding community, truth, and the dichotomy between animal laborans and homo faber, are uniquely suited, as well as relatively under considered, when it comes to revising the marketplace approach.